TECHNO MATHEMATICS LITERACY MAHASISWA CALON GURU PADA MATERI STATISTIKA PENELITIAN DI IKIP SILIWANGI : SEBUAH ANALISIS - Luvy Sylviana Zanthy; Masta Hutajulu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was to analyze the Techno mathematics Literacy of non-Mathematics Education Teacher Candidate students in the Research Statistics course. This research is a qualitative descriptive study. The research subjects were 100 non-Mathematics Education students who taught the Research Statistics Course in the Odd Semester of the 2022/2023 Academic Year. Data on learning activities were obtained from the implementation of learning using observation guidelines and data on learning evaluation were obtained from learning evaluation activities based on tests of students' mathematical literacy abilities in the form of document studies, response questionnaires and interview sheets. Based on the results of the study, it can be concluded that the average ability of Techno Mathematics Literacy in the aspects of data literacy, Sense of errors and sense of numbers, and Creative aspects and ability to draw is included in the poor category, while the ability to use computer software and aspects of communication skills are in the Adequate category. Overall, the average Techno Mathematics Literacy of non-Mathematics Education prospective teacher students at IKIP Siliwangi is in the poor category.